Solid anaerobic digestion batch with liquid digestate recirculation and wet anaerobic digestion of organic waste: Comparison of system performances and identification of microbial guilds. (January 2017) - Di Maria, Francesco; Barratta, Martino; Bianconi, Francesco; Placidi, Pisana; Passeri, Daniele
Highlights: Performances and methanogenic pathway of SADB and wet AD of organic waste were analyzed. Liquid digestate recirculation improved AD even at TS > 30%. Methane yields were SADB = 252 NLCH4 /kgVS wet AD = 320 NLCH4 /kgVS. Large syntrophic metabolism was detected in the liquid phase of SADB. Abstract: Solid anaerobic digestion batch (SADB) with liquid digestate recirculation and wet anaerobic digestion of organic waste were experimentally investigated. SADB was operated at an organic loading rate (OLR) of 4.55 kgVS/m 3  day, generating about 252 NL CH4 /kgVS, whereas the wet digester was operated at an OLR of 0.9 kgVS/m 3  day, generating about 320 NL CH4 /kgVS. The initial total volatile fatty acids concentrations for SADB and wet digestion were about 12, 500 mg/L and 4500 mg/L, respectively. There were higher concentrations of ammonium and COD for the SADB compared to the wet one. The genomic analysis performed by high throughput sequencing returned a number of sequences for each sample ranging from 110, 619 to 373, 307. More than 93% were assigned to the Bacteria domain. Seven and nine major phyla were sequenced for the SADB and wet digestion, respectively, with Bacteroidetes, Firmicutes and Proteobacteria being the dominant phyla in both digesters. Taxonomic profiles suggested a methanogenic pathway characterized by a relevant syntrophic acetate-oxidizing metabolism mainly in the liquid digestate of the SADB. This result also confirms the benefits of liquid digestate recirculation for improving the efficiency of AD performed with high solids (>30%w/w) content.